Late Cenozoic Foraminifera from diamictites of Cape Lamb, Vega Island, Antarctic Peninsula - Carames, Andrea Alejandra; Concheyro, Graciela
Abstract. Foraminiferal assemblages recovered from Cape Lamb sediments on Vega Island are examined and illustrated herein. The foraminifera were discovered in Cenozoic debris and palagonitic breccia lithofacies that crop out at the southwestern tip of Cape Lamb. Among all the Cenozoic diamictite deposits recognized in this island, the studied sediments are the youngest and the most fossiliferous. Pectinids, brachiopods, and microfaunas are exceptionally well preserved and indicate little or no transport. The foraminiferal assemblage is dominated by infaunal species, with the most abundant including Globocassidulina biora, Cribroelphidium sp. aff. E. excavatum, and Cassidulinoides parkerianus, and the epifaunal Cibicides refulgens. These foraminifera suggest a normal inner shelf marine environment. Microfossils and macrofauna, stratigraphical evidence observed in the field and published isotopic ages from the nearby Cape Lamb suggest a Pleistocene age for this deposit. Resumen. Foraminíferos del Cenozoico Tardío, Cabo Lamb, Isla Vega, Península Antártica. Se examina e ilustra la microfauna de foraminíferos recuperada de sedimentitas del Cabo Lamb, Isla Vega. La asociación estudiada se halló en una acumulación cenozoica compuesta por fragmentos rocosos y brechas palagoníticas, que aflora en el extremo sudoeste del cabo Lamb. Estas sedimentitas, son las diamictitas cenozoicas más jóvenes y más fosilíferas reconocidas en la isla y al presentar una excepcional preservación de pectínidos y braquiópodos, llamaron la atención como probables hospedadoras de microfaunas que habrían sufrido poco transporte. La asociación de foraminíferos es dominada por especies infaunales como Globocassidulina biora, Cribroelphidium sp. aff. E. excavatum y Cas- sidulinoides parkerianus, y el epifaunal Cibicides refulgens. Los foraminíferos sugieren un ambiente marino normal de plataforma interna. microfósiles, macrofauna, evidencias estratigráficas que surgen de las observaciones de campo y edades isotópicas obtenidas para depósitos muy ...